Apropriações e práticas do espaço urbano: o pedalar como momento de protesto - Sampaio, Tiago Saboia de Albuquerque (2015)
Based on an ethnographic perspective - of an intersubjective and lasting contact with a collective of bicycle users in the city of Fortaleza -, in this research, I aim to investigate and reflect about the urban cycling universe, with special emphasis on its inherent relationship and articulation with the uses and (re) significations of the city's public spaces; the different - and sometimes conflicting - ways of "doing politics" and of enjoying and building the urban space from the use of the bicycle as a form of transportation. For this reason I depart from the daily narratives, representations and practices of pro-bicycle activism and the experiences of urban cyclists that orbit around three collectives of promoting and defending the bicycle as a form of transportation in the city : The collective Massa Crítica, the Association of Cyclists in the City of Fortaleza - the Ciclovida - and the Bike Angel Project. The daily practices and activism of these individuals are perceived by themselves as a "politicization" of the theme - increasingly on the agenda - of urban mobility and circulation, also relating, more broadly, to the way of perceiving and experiencing the city and its spaces. What this research points out is that specific conceptions about the spaces and temporality of the city are linked to a specific form - a counter-use - of fruition and use of urban space. In the case of urban cyclists, what is very characteristic is that emerges, the more the practice is continuous, the more and more a perspective of "re-conquering" and "(re) approaching the city" - the public space, the other city people, the unexpected, casual encounters - and "make it a better place by bicycle".